The Hierarchical Procedures of Writing A Well Articulated Quantitative Academic Paper - S, Abdulrahman; ., Musa (International Journal of Business and Management Future, 2018)
The study examined the logical stages of writing a well-articulated quantitative academic paper based on reviewing a well scholarly write ups. The paper is a conceptualised article that restricted itself within the saying and perceptions of the worldwide recognised scholars from the field of research methodology. As a researcher in the field of research, his abstract is expected to constitute of 7 points namely: Objectives, methodology, major findings, policy implication, and contribution to knowledge, major critics, and frontier of research.